Assessing adaptation options for climate change: A guide for coastal communities in the Coral Triangle of the Pacific 8. Implementation planning - WorldFish (2013)
Assessing options for adapting to climate change is an important part of building resilient fishing and farming communities. This brochure is part of a series that collectively detail how a community-based assessment of climate change was used in partnership with coastal communities and provincial and national-level stakeholders in Timor-Leste and Solomon Islands. The assessment contains four distinct, but related, steps (Fig 1) focused on supporting community-level decision-making for adaptation through a series of participatory action research activities. Each brochure in this series details a specific activity in the four-step assessment. This series of eight brochures is primarily aimed for use where resources are limited or where it is more appropriate to use a rapid, qualitative and non-data intensive method of assessment. Community leaders, local NGOs and regional and national-level government representatives in developing countries may find this series useful. In this brochure we provide details of an activity relating to the ‘Planning implementation’ step of the assessment, namely a workshop held with community members to evaluate the usefulness of the material produced to date on climate change adaptation and how to begin planning the implementation of selected adaptation actions. More specifically, the following questions were posed: • Were the outputs of the participatory workshops and multidisciplinary research relevant and/or useful to communities in making decisions about how and when to adapt to a changing climate (Fig 2)? • Is there any further information needed to allow informed decisions to be made by the community about how they can adapt? • What are the social, economic and environmental tipping points or thresholds that would trigger the need to implement adaptation actions (Fig 3)? • Who are the key people or institutions that communities need to work with to ensure adaptation actions are implemented and maintained effectively?